Role of asbestos clearance in explaining long-term risk of pleural and peritoneal cancer: a pooled analysis of cohort studies. Issue 9 (14th August 2019) - Barone-Adesi, Francesco; Ferrante, Daniela; Chellini, Elisabetta; Merler, Enzo; Pavone, Venere; Silvestri, Stefano; Miligi, Lucia; Gorini, Giuseppe; Bressan, Vittoria; Girardi, Paolo; Ancona, Laura; Romeo, Elisa; et al.
Abstract : Objectives: Models based on the multistage theory of cancer predict that rates of malignant mesothelioma continuously increase with time since first exposure (TSFE) to asbestos, even after the end of external exposure. However, recent epidemiological studies suggest that mesothelioma rates level off many years after first exposure to asbestos. A gradual clearance of asbestos from the lungs has been suggested as a possible explanation for this phenomenon. We analysed long-term trends of pleural and peritoneal cancer mortality in subjects exposed to asbestos to evaluate whether such trends were consistent with the clearance hypothesis. Methods: We used data from a pool of 43 Italian asbestos cohorts (51 801 subjects). The role of asbestos clearance was explored using the traditional mesothelioma multistage model, generalised to include a term representing elimination of fibres over time. Results: Rates of pleural cancer increased until 40 years of TSFE, but remained stable thereafter. On the other hand, we observed a monotonic increase of peritoneal cancer with TSFE. The model taking into account asbestos clearance fitted the data better than the traditional one for pleural (p=0.004) but not for peritoneal (p=0.09) cancer. Conclusions: Rates of pleural cancer do not increase indefinitely after the exposure to asbestos, but eventually reach a plateau. This trend is well described by a model accounting for a gradual elimination of the asbestos fibres. These results are relevant for the prediction of future rates of mesothelioma and in asbestos litigations.